Features of the Relationship between Cardiorhythm Regulation and Components of Internal Picture of Disease in Students - O.E. Elnikova; A.V. Dobrin (Клиническая и специальная психология)
The work is aimed at identifying the features of the mechanisms of regulation of cardiac rhythm, which determine adaptive behavior in situations of health disorders. Materials from two empirical studies conducted on a sample of 1st to 4th year students at Yelets University are presented. The study 1 (N=160) involved respondents aged 17 to 23 years of both sexes, of whom 37.5% had various health problems. In study 2 (N=60), students (average age 21±2.3 years), of which 50% belong to the category of chronically ill, 50% had periodic health problems. Study 2 included five stages, in which four levels of the internal picture of the disease (IPD) were diagnosed and cardiac rhythm measurements were performed at rest and against the background of existing disease memories. The following methods were used: SF-36 Health Status Survey, Health, Activity, and Mood questionnaire, SCL-90-R, “Coping behavior in stressful situations”, “Level of subjective control”, TATD method. The fixation of the heart rate variability was carried out using the hardware and software complex OMEGA-M. The results obtained allow us to say that there is a correlation between the individual components of IPD and the parameters of regulation of heart rate variability. The optimal state of the body's homeostatic systems, which ensure successful adaptation, is characterized by the activity of the parasympathetic department of autonomic nervous system in the process of cardioregulation.